Increasing the accuracy of measuring the physicochemical parameters of wastewater samples when implementing a new informative method - Sebko, V. V.; Zdorenko, V. G.; Zashchepkina, N. M.; Barylko, S. V. (World academy of materials and manufacturing engineering, 2023)
The necessity of developing new multi-parameter electromagnetic methods to obtain the information on controlled wastewater samples from fruit juice production has been proved. Based on the universal transformation functions G = f(x) and φ = f(x) obtained in the work, which relates the amplitude and phase components of the multi-parameter MFP signal with the parameters of wastewater samples, a three-parameter method for joint measurement control of the electrical conductivity χ, relative dielectric constant εr and temperature t of wastewater samples from the production of apple juice. An algorithm for joint multi-parameter measurements of the parameters χ, εr and t based on a transformer electromagnetic transducer (MFP) has been developed, the switching scheme provides for heating a wastewater sample during measurement control to simulate production conditions. Since the amplitude and phase components of the MFP multi-parameter signal depend on the temperature t, sample heating also makes it possible to create information redundancy and improve the accuracy of wastewater sample identification. The implementation of the proposed method makes it possible to indirectly determine the composition of wastewater samples, using only one transducer with known physical properties, all this leads to an increase in the accuracy of measuring the parameters of wastewater samples in comparison with reference methods and measuring instruments and ultimately allows choosing a promising method of wastewater treatment in accordance with the analysis of experimental data. The data obtained indicate the acidic composition of wastewater; therefore, it is proposed to neutralise industrial waste at the outlet of the finished product. The methodology of the above studies lies in the fact that, within the framework of a scientific approach, it is necessary to expand the functional and technical capabilities of the electromagnetic device by implementing a new multi-parameter electromagnetic method for joint measurements of the physicochemical parameters of wastewater samples. Design/methodology/approach: The essence of the proposed three-parameter method of joint measurement control of parameters χt, εr and t is based on the analysis of the interaction of an external homogeneous magnetic field with the magnetic field of eddy currents induced in a conductive electrolytic liquid (in a wastewater sample). Based on the input of special normalised parameters, as well as the obtained universal transformation functions G = f(x) and φ = f(x), which relate the physicochemical parameters χ, εr and t of the electrolytic liquid medium (wastewater samples from apple juice production) with the amplitude and phase components of the multi-parameter signal MFP, at a constant frequency of the magnetic field f, Increasing the accuracy of measuring the physicochemical parameters of wastewater samples when implementing the implementation of a three-parameter electromagnetic method of joint measurement control of the electrical conductivity χ, relative permittivity εr and temperature t have been proposed. At the same time, using the thermal MFP switching circuit, it is necessary to measure two magnetic fluxes: the reference magnetic flux F0 in the absence of a glass tube with liquid in the converter and the magnetic flux F2 (if there is a wastewater sample in the converter) and the phase angle φ between the flows F0 and F2. To this end, three wastewater parameters, χt, εr and t, are determined jointly by the same MFP in the same control zone. Implementing the proposed method makes it possible to indirectly assess the composition of wastewater, select a promising treatment method, and then take preventive measures related to environmental protection. Findings: The possibility of applying the MFP operating theory to the realisation of an informative three-parameter electromagnetic method of joint measurements of specific conductivity χ, relative permittivity εr and temperature t parameters of wastewater has been studied. An algorithm for modelling the process of joint multi-parameter measurements of specific conductivity χ, relative permittivity εr and temperature t based on MFP has been developed. The basic relations describing a three-parameter method of joint measurements of specific conductivity χ, relative permittivity εr and temperature t of controlled wastewater samples are presented. The obtained numerical values of the physicochemical parameters of the wastewater sample are in good agreement with the data obtained using the controlling methods. Implementation of the proposed three-parameter method allows to increase in the accuracy of identification of wastewater samples due to the obtained multi-parameter information, as well as to determine indirectly the composition of wastewater samples, using a single transducer with certain physical properties; all this leads to increased accuracy of wastewater sample parameters in comparison with the reference methods and measuring tools, and allows to choose a rational and inexpensive treatment method. Research limitations/implications: The method studied has the following limitations: the range of variation of the diameters is 20 mm to 55 mm. The lower limit is set by the frequency of the electromagnetic field, and the upper limit by the diameter of the transducer frame, 57 mm. Measurements are made in homogeneous longitudinal magnetic fields, and the length of the MFP winding must be ten times the diameter to achieve such field homogeneity. The sample length must be greater than or equal to the winding length of the transducer, i.e., lo⩾ ln. The radial misalignment of the product does not affect the measurement results, as the magnetic field of the transducer is homogeneous. The MFP frame limits product misalignment. It is found that sample misalignment in the range of ±4% to 6% has no practical effect on the measurement results of physicochemical parameters of wastewater samples. The change in temperature causes a change in the resistance r of the magnetising winding, so the windings of the converter must be thermally insulated from the environment (wrapped with mitre tape, coated with BF-19 adhesive and then this structure is baked at the temperature t = 300°C in the EKPS-500 muffle furnace). Practical implications: The practical significance of the work lies in the fact that as a result of the analysis of the obtained values of the physicochemical parameters of wastewater samples, it is possible to timely prevent the reasons for the deviation of wastewater from the specified indicators of international standards governing the discharge of wastewater into the city sewerage and to take measures to prevent pollution of artificial and natural reservoirs located in the residential areas, as well as to develop effective methods of wastewater treatment of food and processing industries. The obtained relations, which describe the universal transformation functions G = f(x) and φ = f(x), algorithms for measuring and calculating operations for determining the specific electrical conductivity χ, relative permittivity εr and temperature t of wastewater samples based on MFP, make it possible to design, construct and create automated measuring installations based on intelligent devices that have a phenomenological approach to the measuring control of physical and chemical parameters of electrolytic liquid media as the basis of their operating theory. Originality/value: The electromagnetic transducer (EMT) theory has been further developed with a sample of a weak electrolytic liquid with an acidic composition (a sample of wastewater from apple juice production).
Keywords: non-contact eddy current method; three-parameter informative method; physicochemical parameters of wastewater; wastewater sample; eddy current transducer